Two new species of Oxyethira Eaton 1873 (Trichoptera: Hydroptilidae) from Roraima state, Brazil - Neto, Jaime De Liege Gama; Passos, Mahedy Araujo Bastos (Zootaxa, 2022)
Two new species of Oxyethira from Brazil are described: Oxyethira (Dampfitrichia) jiquitaia sp. nov., and Oxyethira (Tanytrichia) librina sp. nov. Illustrations of male genitalia are provided with each description. These results increase the number of Oxyethira species in Brazil from 37 to 39.